Preliminary sizing of large propeller driven aeroplanes - Dieter Scholz and Mihaela Niţă (Předběžný výpočet rozměrů velkého vrtulového letounu, 2009)
Different types of aeroplanes (small / large, propeller / jet) require their own type of preliminary sizing method. One of theses methods differs only in a few but important aspects from the other. For the sake of efficient teaching of students and easy application in practice, the authors ask for the definition of a set of clearly defined step by step preliminary sizing methods. Based on the rather well known sizing method for large jet aeroplanes, the paper derives a preliminary sizing method for large propeller driven aeroplanes. In this way the paper tries to contribute to the definition of the set of methods. The sizing methods are all based on a matching chart that helps to graphically solve a two-dimensional optimization problem. The matching chart draws the optimization variable thrust-to-weight ratio (for jets) respectively power to mass ratio (propeller driven planes) versus wing loading for all basic requirements, which the aeroplane has to fulfill. The sizing method for propeller driven large aeroplanes is explained in detail and applied to a redesign study of the ATR 72. All equations are given in a form readily available for use. This requires in some cases the evaluation of proportionality factors based on aircraft statistics. Given are factors taking into account statistics for landing distance, take-off distance and maximum glide ratio for large propeller driven passenger aircraft. Furthermore, generic equations for the variation of power with altitude and speed of turboprop engines is given as well as a chart to determine the propeller efficiency.
Keywords: aircraft; design; preliminary sizing; matching chart; propeller; ATR 72; redesign